Pengaruh Fomo, Gaya Hidup Terhadap perilaku konsumtif Mahasiswa FakultasEknomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara - Aulia Zahra; Umi Khairani; Dini Lestari (Universitas Muhammadiyah Enrekang, 2023)
The existence of humans living in metropolitan areas is a peculiarity that encourages humans to pursue the latest directions that can trigger inappropriate behavior in humans. The research aims to determine how much significant influence lifestyle has on consumer behavior in the Management study program, Faculty of Economics and Islamic Business, State Islamic University of North Sumatra. In this study, the sample used was students at the Faculty of Islamic Economics and Business, majoring in management, Islamic economics, Islamic accounting, Islamic banking, Islamic insurance, State Islamic University of North Sumatra, with a target of a maximum of 115 respondents. This type of research is quantitative research. This research method is a correlation method. This research was designed to determine the relationship between the variables studied, so this research is called correlational research, to obtain the overall data in this study, the researchers used data collection techniques with questionnaires and documentation. In this study there are two variables to be examined, namely the variable (X) Lifestyle which is the independent variable and the variable (Y) Student Consumptive Behavior which is the dependent variable. < 0.356 > 0.2393) so there is a significant influence between lifestyle on consumptive behavior of students at the Islamic Faculty of Economics and Business, State Islamic University of North Sumatra. This is because r count (0.356) is greater than r table at a significant level of 5% and 1% thus Ha is accepted and Ho is rejected, which means that lifestyle has a significant effect on the consumptive behavior of students at the Faculty of Economics and Islamic Business, State Islamic University of North Sumatra . The magnitude of the influence of student consumptive behavior at the Islamic Faculty of Economics and Business, State Islamic University of North Sumatra is 12.7%, while the remaining 87.3% is influenced by other variables not included in this study